Research on Longitudinal Precise Parking Control of Unmanned Vehicles in Open-pit Mines - ZHANG Qian; WANG Bin; YUAN Xiwen (Kongzhi Yu Xinxi Jishu)
At present, under the complex road conditions in the mining area, there are a series of phenomena such as slippage, collision with the retaining wall and sudden braking when open-pit mine transportation vehicles are automatically driven and unloaded, which seriously affects the longitudinal and precise parking of vehicles. In this regard, this paper proposes a distributed longitudinal adaptive precise parking control strategy for open-pit mine transportation vehicles. First, the upper-layer controller calculates the expected acceleration of the vehicle according to the state feedback tracking control method, and adds slope resistance and rolling friction to calculate the theoretical acceleration of the vehicle. Then, the lower-layer controller uses inverse dynamics to control the accelerator opening and electrical braking percentage to achieve stable vehicle speed during reversing. Field test results show that the distributed control method designed in this paper can greatly improve the problems of rolling, collision with the retaining wall and sudden braking due to high speed, and realize the parking accuracy of only 0.19 m from the end point, which has a greater improvement than the 0.50 m parking accuracy of the "feedforward + PI control" strategy.